Prediagnostic Prostate-specific Antigen Testing and Clinical Characteristics in Men with Lethal Prostate Cancer - Markus Arvendell; Lars Björnebo; Martin Eklund; Ugo Giovanni Falagario; Jan Chandra Engel; Olof Akre; Henrik Grönberg; Tobias Nordström; Anna Lantz (European Urology Open Science, 2024)
Background and objective: Prostate cancer (PC) is the fifth leading cause of cancer-related mortality in men worldwide. Opportunistic testing with prostate-specific antigen (PSA) has limited impact on PC mortality. Our objective was to assess prediagnostic PSA testing patterns and clinical characteristics at diagnosis in men with lethal PC. Methods: We conducted a population-based observational study of all men dying from PC in Stockholm County, Sweden, from 2015 to 2019. Data were retrieved from the National Prostate Cancer Register and the Stockholm PSA and Biopsy Register. If the first PSA was registered within 1 yr before diagnosis, men were categorised as PSA naïve. If an elevated PSA level was registered >1 yr before diagnosis without leading to prostate biopsy or repeating PSA within 1 yr, men were categorised as having delayed diagnosis. If a normal PSA level was registered within 5 yr before diagnosis, followed by an elevated PSA level that resulted in PC diagnosis within 1 yr, men were categorised as PSA tested. Clinical characteristics at diagnosis were stratified with D’Amico risk group classification. Key findings and limitations: Among 1473 men dying from PC, PSA test history was available for 995. Of these men, 60% (n = 592) were PSA naïve, 25% (n = 250) received delayed diagnosis, and 15% (n = 153) were PSA tested. After examining all 1473 men, 25% (n = 350) were diagnosed with low- or intermediate-risk cancer, 48% (n = 687) with high-risk cancer, and 27% (n = 385) with metastatic disease. Limitations include the retrospective design. Conclusions and clinical implications: Many men with lethal PC lacked PSA testing before diagnosis or had been tested without subsequent follow-up. Nearly half of the study population was diagnosed with high-risk cancer and almost one-third with metastatic disease. These findings suggest further evaluation of the current opportunistic PSA testing approach. Patient summary: Data from a population-based observational study of men dying from prostate cancer showed that many of them did not undergo either prostate-specific antigen (PSA) testing before diagnosis or subsequent follow-up if tested. These findings implicate deficiencies in the current opportunistic PSA testing approach.